AN INTERPRETATION OF MEANING QASAM IN AL-QUR’AN - Daib Insan Labib, Muhammad Alfreda; Fajriyaturrohmah, Fajriyaturrohmah (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This article discusses interpretation qasam in al-Qur’an. qasam has an important position and role in al-Qur’an. The reason qasam often used as a form taukīd from the sentence intended by Allah. The method in this research is qualitative. In processing the data, the researcher used a descriptive-analysis method, namely explaining the data that had been collected and then analyzing the data to achieve the research objectives. Some of the discussions in this study include definitions and sighat qasam, benefits and muqsam bīh in the Qur'an, all kinds of things qasam, regarding muqsam 'alaih, and conditions qasam. One of the conclusions in this research is the explanation that qasam is a ta’kīd (amplifier) ​​which is famous for emphasizing the truth of what we say and strengthening the truth in the soul